Completeness of the ZW and ZX calculi - Ng, K (2018)
This thesis looks at two quantum motivated graphical calculi, the ZW calculus and ZX calculus. These two calculi are intended to perform qubit calculations using string diagrams. Both calculi are universal in the sense that they are able to represent all qubit maps, but they lack the completeness which means that they don't allow all qubit computation. The main goal of the thesis is to address the completeness issue. The ZW calculus was completed by Hadzihasanovic in his DPhil thesis. We build on his work to do a completion for a fragment of the ZW calculus which describes operations in the fermionic quantum circuits. In the process, we discovered an important family of maps, the even and odd projectors. The even projectors is particularly important for the completion process. Next, we further restrict the calculus to only "even" maps and complete this fragment too. The odd projectors are important for this completion process. We give an interesting story for the even fragment ZW calculus: it describes a world without "real" particles, and the fermionic particles are manifestation of the curvature of spacetime and self 'fermionic' intersection and interaction of spacetime. The ZX calculus was not complete and we solve this issue in this thesis. The technique used is a refinement of the one used in the paper on 'A Complete Axiomatisation of the ZX-Calculus for Clifford+T Quantum Mechanics' by Jeandel, Perdrix, and Vilmart. The basic idea of the technique is to translate the ZX calculus to the ZW calculus to analyse the problem, then translate it back. We also obtained many interesting generalising results which includes the completeness for the Clifford+T fragment and any fragments containing the Clifford+T fragment. Finally, we end off with some interesting possible continuation of the thesis. Many of them are low hanging fruits. One of them is the extension of the calculi to represent qudits maps. The other is to generalise the ZW calculus to take semi-ring parameters which may be suited for other areas of computer science.